2000
DOI: 10.1002/etc.5620190125
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of total dissolved solids associated with two mine effluents to chironomid larvae and early life stages of rainbow trout

Abstract: Abstract-Assessment of total dissolved solids (TDS) represents an integrated measure of the concentrations of common ions (e.g., sodium, potassium, calcium, magnesium, chloride, sulfate, and bicarbonate) in freshwaters. Toxicity related to these ions is due to the specific combination and concentration of ions and is not predictable from TDS concentrations. Short-term chronic toxicity tests were conducted with larval chironomids and trout (eggs and swim-up fry) to assess their TDS tolerance relative to effluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 8 publications
5
67
0
1
Order By: Relevance
“…Soucek and Kennedy (2005) observed lethal effects of sulfate to H. azteca (512 mg/L), C. dubia (2,050 mg/L), and C. tentans (14,134 mg/L). Chapman et al (2000) also found reductions in survival and growth of C.…”
Section: Introductionmentioning
confidence: 84%
“…Soucek and Kennedy (2005) observed lethal effects of sulfate to H. azteca (512 mg/L), C. dubia (2,050 mg/L), and C. tentans (14,134 mg/L). Chapman et al (2000) also found reductions in survival and growth of C.…”
Section: Introductionmentioning
confidence: 84%
“…To test the models with more field-relevant ion compositions, additional toxicity tests were conducted on synthetic waters patterned after effluents and surface waters with anthropogenic elevations of major ions. Various published data [11][12][13][14][15][16][17][18][19] and some unpublished data of the authors were examined and used to formulate 10 test waters that encompassed the range of variability observed for cation and anion ratios from these sources and which were feasible to prepare in the laboratory. Table 1 provides the fractional cation and anion concentrations (on a molar basis) in these "field-based mixtures."…”
Section: Model Parameterizationmentioning
confidence: 99%
“…… This impairs the use of the streams and ultimately leads to listing of these streams as 'impaired water bodies' in EPA's water quality reports …'' (Pomponio 2009). Several recent studies (Chapman et al 2000;Goodfellow et al 2009;Pond et al 2008;Timpano et al 2010) have addressed the issue of TDS as a major stressor upon receiving streams in mined watersheds and are discussed in more detail later in this paper. More recent EPA guidance (issued in 2011; subsequently withdrawn) was based on the belief that mine discharges with EC levels\300 ls/cm generally will not cause significant degradation of the aquatic ecosystem while instream conductivity levels [500 ls/cm are likely to be associated with significant adverse impacts on the aquatic ecosystem.…”
Section: Background On Spoil Weathering and Tds Sourcesmentioning
confidence: 99%